Bile Acids Alter the Autophagy and Mitogenesis in Skeletal Muscle Cells - Valero-Breton, M; Cabello-Verrugio, C; Tacchi, F; Orozco-Aguilar, J (Springer, 2023)
Muscle atrophy decreases muscle mass with the subsequent loss of muscle function. Among the mechanisms that trigger sarcopenia is mitochondrial dysfunction. Mitochondria, whose primary function is to produce ATP, are dynamic organelles that present the process of formation (mitogenesis) and elimination (mitophagy). Failure of any of these processes contributes to mitochondrial malfunction. Mitogenesis is mainly controlled by Peroxisome proliferator-activated receptor-gamma coactivator-1alpha (PGC-1α), a transcriptional coactivator that regulates the expression of TFAM, which participates in mitogenesis. Mitophagy is a process of selective autophagy. Autophagy corresponds to a degradative pathway of protein complexes and organelles. Liver disease caused sarcopenia and increased bile acids in the blood. We demonstrated that the treatment with cholic (CA) or deoxycholic (DCA) bile acids generates mitochondrial dysfunction and loss of biomass. This work assessed whether CA and DCA alter autophagy and mitogenesis. For this, western blot evaluated the autophagy process by determining the protein levels of the LC3II/LC3I ratio. In addition, we assessed mitogenesis using a luciferase-coupled plasmid reporter for the PGC-1α promoter and the protein levels of TFAM by western blot. Our results indicate that treatment with CA or DCA induces autophagy, represented by an increase in the LC3II/LC3I ratio. In addition, a decreased autophagic flux was observed. On the other hand, when treated with CA or DCA, a decrease in the activity of the PGC-1α promoter was observed. However, the levels of TFAM increased in myotubes incubated with CA and DCA. Our results demonstrate that CA and DCA modulate autophagy ad mitogenesis in C2C12 myotubes. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.